THE EFFECTS OF LOGICAL THINKING AND VOCABULARY MASTERY TOWARDS STUDENTSâ READING COMPREHENSION AT STATE SENIOR HIGH SCHOOL IN EAST JAKARTA - mulyadi, mulyadi (JURNAL SMART, 2017)
ABSTRACTThe aim of this research is to find out and analyze empirically the effects of logical thinking and vocabulary mastery towards studentsâ reading comprehension. Research method used was survey. The observed population of this research is twelfth grade students from SMA Negeri 88, SMA Negeri 98 and SMA Negeri 106 in East Jakarta.The sample was taken through simple random sampling and 60 students as samples of this research. For collecting data, the instruments used in this research were tests (multiple choices) to measure Logical thinking, vocabulary mastery and reading comprehension.Â  The data then was analyzed by using descriptive statistics, multiple correlation coefficient, and determination coefficient and regression analysis. Previously, the requirements test has been accomplished before analyzing the data, such as normality and linearity test. The result of this research explained that there is significant effect of logical thinking and vocabulary mastery concurrently toward studentsâ reading comprehension with correlation coefficient 0,901 and determination coefficient 0,812 or 81,2%. The regression equation is stated Å¶=17.894+0.543X1+0.386X2. The result has also shown Fobserved =122,732 > 3,16 (Ftable) and Sig= 0,000 < 0,05.Partially, there is significant effect of logical thinking towards studentsâ reading comprehension. The result has shown the score of Sig = 0,000 < 0,05 and ttest = 4,324. There is significant effect of vocabulary mastery towards studentsâ reading comprehension. The result has shown the score of Sig= 0,000 < 0,05 and ttest = 3,924.Keywords: Logical Thinking, Vocabulary Mastery and Reading Comprehension